The effects of accounting knowledge, entrepreneurial traits, and subjective norms on the use of accounting information in investment decision making (case study on MSME actors in Gunungkidul Regency) - Firdha Rahmiyanti; Reza Adellya Pratiwi; Heny Yuningrum; Muyassarah Muyassarah (Journal of Islamic Accounting and Finance Research, 2020)
Purpose - The purpose of this study is to determine the effects of accounting knowledge, entrepreneurial traits, and subjective norms on the use of accounting information on making investment decisions of MSME actors in Gunungkidul Regency.Method - This study uses quantitative research methodology by purposive sampling. The gathered data in this study were processed using the SPSS program. This study was carried out on 20 February to 20 March 2020. The population in this study was businessmen of MSMEs in Gunungkidul Regency who had used accounting documentation. The research took 60 respondents as a sample of the study.  Result - This study resulted that the variables of accounting knowledge and entrepreneurial traits have a positive and significant effect on the use of accounting information in making investment decisions of MSME actors in Gunungkidul Regency; While the subjective norms variable does not have a positive and significant effect on the use of accounting information in making investment decisions of MSME actors in the Gunungkidul Regency.Implication - Future research can expand the object of research in several other regencies and can add other research variables.Originality - The researchers added an independent variable that is subjective norms and entrepreneurial traits, whereas the previous researchers only used accounting knowledge as the independent variable.